Ethics and integrity in visual research methods - Dodd, Savannah (Advances in research ethics and integrity ;, 2020)
Ethics and Integrity in Visual Research Methods aims to unpack the multiple considerations for ethics and integrity that accompany research methods involving visual data generation and analysis. This volume focuses on the media of photography and film. Contributing authors cover a variety of topics, including: consent and dignity when working with vulnerable and marginalized populations; the limitations of participatory methods within a context of inequity and postcolonialism; the challenges of anonymising visual data; and the risks of sharing visual data online. The authors share their experiences of working with visual methods across a range of contexts, making recommendations for best practice. This volume is intended to be practical, and the key messages aim to be concrete and applicable for anyone embarking on visual methods research.